Coal facies of the Middle Permian Baruunnaran deposit, South Mongolia - Demberelsuren, Batbold; Jargal, Luvsanchultem; Munkhtsengel, Baatar; Lkhagva-Ochir, Said; Ganzorig, Ranjin; Tsolmon, Adiya; Enkhbat, Chuluunbat; Turbat, Erdenebat; Tuvshinbayar, Enkhtuvshin; Tugsjargal, Ariya (Mongolian Geoscientist, 2023)
The Baruunnaran coal deposit is located in the northeastern part of the South Gobi Basin, southern Mongolia, and hosted in the middle Permian Tavantolgoi Formation. In this paper we present indices of coal facies determined from 34 coal samples obtained from three seams in the lower and upper part of the formation (III, IXG and X), by studying their organic petrography and the geochemistry of the coal ash. The results of coal petrography revealed that seams III, IXG and X are composed of 46.9-80.9 vol.% vitrinite, 11.6-47.5 vol.% inertinite and 1.2-18.2 vol.% liptinite. In samples from seams III and X the average content of mineral matter is low at 11 and 13.4 vol.%, respectively, and 6.3 vol.% in seam IXG, and consists of clay, silica, pyrite, carbonate, and other minerals. The inorganic content mostly occurs as fillings of cell cavities, cracks, and fissures of vitrinite and inertinite macerals. The vitrinite random reflectance values range from 0.81-1.07%. The Gelification Index and Tissue Preservation Index suggest the peats accumulated in wet forest swamp environments with high tree density. The majority of the seams accumulated in mildly oxic to anoxic conditions with good tissue preservation. The peat mire water ranged from weakly to strongly acidic. Further, it was determined by Al2O3/TiO2 ratios that the clastic sediments were probably sourced from volcanic basement characterized by intermediate felsic composition.